Sephardic epitaphs in Hamburg's oldest jewish cemetery: poetry, riddles, and eccentric texts - Sárraga, Marian (AJS review, 2002)
The Sephardic community of Hamburg was founded by Portuguese conversos who had settled in the Hamburg area during the three decades prior to 1611. In that year, after receiving permission to form a Jewish community in Hamburg, the conversos purchased from Christian IV, king of Denmark, a tract of land near the town of Altona for use as a cemetery. During most of the time period discussed in this article, Altona was under the crown of Denmark, while Hamburg was an independent Hanseatic city ruled by a senate of burghers. Today, Altona is a district of the city of Hamburg, within walking distance of the city's historic center.